Small firms and domestic bank dependence in Europe's Great Recession - Mathias Hoffmann; Egor Maslov; Bent E. Sørensen (University of Zurich, Department of Economics, 2021)
After the inception of the euro, the real economy in most member countries remained dependent on credit by domestic banks, which increasingly funded themselves through cross-border interbank funding. We find that this pattern of 'double-decker' banking integration exposed domestic banks to sharp declines in cross-border interbank lending during the eurozone crisis. As a result, domestic banks reduced lending which led to large declines in output in sectors with many small (bank-dependent) firms. We propose a quantitative small open economy model to account for these patterns and conclude that a global banking shock leading to a sudden stop in cross-border interbank lending in the eurozone is required to account for them.
Keywords: F30; F36; F40; F45; 330; Small and medium enterprises; sme access to finance; banking integration; domestic bank dependence; interbank dependence; international transmission; eurozone crisis